2019
DOI: 10.3390/rs11141682
|View full text |Cite
|
Sign up to set email alerts
|

Wind Speed Retrieval from Simulated RADARSAT Constellation Mission Compact Polarimetry SAR Data for Marine Application

Abstract: RADARSAT Constellation Mission (RCM) compact polarimetry (CP) data were simulated using 504 RADARSAT-2 quad-pol SAR images. These images were used to samples CP data in three RCM modes to build a data set with co-located ocean wind vector observations from in situ buoys on the West and East coasts of Canada. Wind speeds up to 18 m/s were included. CP and linear polarization parameters were related to the C-band model (CMOD) geophysical model functions CMOD-IFR2 and CMOD5n. These were evaluated for their wind r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…1a and 1b. Previous studies have reported that s 0 RR is more dependent on wind speed than s 0 RH , s 0 RV , and s 0 RL (Geldsetzer et al 2015;G. Zhang et al 2019); thus, we suggest that s 0 RR is appropriate for high wind speed retrieval.…”
Section: B Statistical Validationmentioning
confidence: 56%
See 2 more Smart Citations
“…1a and 1b. Previous studies have reported that s 0 RR is more dependent on wind speed than s 0 RH , s 0 RV , and s 0 RL (Geldsetzer et al 2015;G. Zhang et al 2019); thus, we suggest that s 0 RR is appropriate for high wind speed retrieval.…”
Section: B Statistical Validationmentioning
confidence: 56%
“…Previous studies have demonstrated that wind speed can be estimated from the s 0 RR using a combination of CMOD5 and a linear model (Denbina and Collins 2016). Moreover, in terms of wind speed retrieval accuracy, right circular transmit, vertical receive (RV-pol) backscatter (s 0 RV ) was found to be comparable to VV-pol backscatter (s 0 VV ), with CMOD GMFs (Geldsetzer et al 2019). A simple CP wind speed retrieval model has been proposed, relating RR-pol backscatter and the wind speed (Fang et al 2019), which has been further refined by incorporating additional incidence angle dependency (G. Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…When an electromagnetic wave passes from one medium to another, changing, therefore, refraction index, or when it strikes an object such as a radar target and it is reflected, it allows a polarization control to acquire knowledge of the characteristic information about the reflectivity, e.g., the orientation and shape of the reflecting object. In classical radars, i.e., amplitude-only radars, the information about a target is mainly obtained from the energy of the returned pulse; interferometric SAR exploits fully the phase and Doppler information, but not the polarization information of the electromagnetic vector wave-scatterer interrogation process [116][117][118][119].…”
Section: Scattering Mechanisms and Radar Observatory Techniquesmentioning
confidence: 99%
“…In [9], the simulated CP data were related to C-band geophysical model function (CMOD) outputs, and their dependence on radar incidence angle, wind speed, and wind direction was examined. This study was further extended in [10] with a larger simulated RCM CP dataset. Results of [9,10] provided initial guidance to Canada's national SAR wind system for the potential of wind information retrieval using RCM.…”
Section: Introductionmentioning
confidence: 99%